2019
DOI: 10.1097/inf.0000000000002306
|View full text |Cite
|
Sign up to set email alerts
|

Successful Whole Genome Sequencing-guided Treatment of Mycoplasma hominis Ventriculitis in a Preterm Infant

Abstract: We report a case of Mycoplasma hominis ventriculitis in a preterm neonate that was successfully identified with 16S ribosomal ribonucleic acid (16s rRNA) sequencing and whole genome sequencing (WGS) after failure to detect the pathogen with conventional diagnostic methods. The infant required doxycycline with subsequent clearance of the infection and no evidence of drug toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…20 62 The challenge in eradicating MDR-GNB infection using conventional IV antibiotics results in significant mortality that can be as high as 71.3 to 72.6%, particularly in neonatal ventriculitis after neurosurgical procedures. 6 Recently, uncommon nosocomial infections caused by Veillonella parvula , 25 Elizabethkingia anophelis , 15 E. meningoseptica , 22 Streptococcus gallolyticus subspecies pasteurianus , 23 Candida albicans , 36 Aspergillus fumigatus , 19 and Mycoplasma hominis 21 have been reported in patients with neonatal ventriculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 62 The challenge in eradicating MDR-GNB infection using conventional IV antibiotics results in significant mortality that can be as high as 71.3 to 72.6%, particularly in neonatal ventriculitis after neurosurgical procedures. 6 Recently, uncommon nosocomial infections caused by Veillonella parvula , 25 Elizabethkingia anophelis , 15 E. meningoseptica , 22 Streptococcus gallolyticus subspecies pasteurianus , 23 Candida albicans , 36 Aspergillus fumigatus , 19 and Mycoplasma hominis 21 have been reported in patients with neonatal ventriculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Another search on Google Scholar was performed to identify articles published in non-PubMed indexed journals. Seven publications were found, so we finally reviewed 37 texts (20 case reports, 6 case series, 6 7 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 and 11 original articles 2 3 9 38 39 40 41 42 43 44 45 [5 retrospective and 3 epidemiological surveillance studies, 1 prospective observational study, 1 pilot population pharmacokinetic modeling study, and 1 research article]).…”
Section: Methodsmentioning
confidence: 99%
“…showed that isolates possessing the K144R mutation remained fluoroquinolon‐susceptible 38 . This would suggest that the mutation database for genotypic prediction of fluoroquinolone resistance is still incomplete for M. hominis ; however, the absence of mutations may still provide some insight clinically, as demonstrated in a case of M. hominis ventriculitis in a preterm infant that was successfully treated after WGS did not identify any known fluoroquinolone resistance markers 39 …”
Section: Discussionmentioning
confidence: 99%
“…The in-house samples are available at the NCBI BioSample database (BioProject ID: PRJNA587095), where detailed metadata can be found (see Supplementary Table S1 for sample IDs). Of note, the antimicrobial susceptibility testing with VITEK takes at least 72 h and generally requires a pure isolate, whereas sequencing preparation followed by the WGS data analysis can be completed under 48 h and does need to not rely on a pure colony (Scaggs Huang et al, 2019).…”
Section: Public Data Collectionmentioning
confidence: 99%